Control of International Activities of Spiritual Administration of Muslims of European Part of the USSR and Siberia in 1945-1953 by Soviet Government - V. A. Akhmadullin (Научный диалог)
The article is devoted to the analysis of the organization of international activities of the Spiritual administration of Muslims of the European part of the USSR and Siberia in 1945-1953. The issue is how this activity was controlled - primarily by the Council for religious affairs under the Council of People’s Commissars of the USSR / Council of Ministers of the USSR. The relevance of the topic is determined by the need to comprehend the historical experience of management decisions of the Soviet state in the field of foreign policy, which were made based on the potential of the Spiritual management of Muslims of the European part of the USSR and Siberia. For the first time the archival material devoted to this problem is put into circulation. The content of the activities of the Council for religious affairs is covered, which was the most public body of the Soviet state for interaction with the spiritual departments of Muslims in matters of foreign policy, which determines the novelty of the study. On the basis of the analysis of archival documents and literature the system of activity of the Soviet state directed on interaction with Spiritual management of Muslims of the European part of the USSR and Siberia is reconstructed. The effectiveness of the measures taken is characterized. On the basis of the study recommendations that can be used in modern practice of public administration in this area are given.